Exploring the impact of a liquefied petroleum gas intervention on time use in rural Peru: A mixed methods study on perceptions, use, and implications of time savings. (December 2020) - Williams, Kendra N.; Kephart, Josiah L.; Fandiño-Del-Rio, Magdalena; Simkovich, Suzanne M.; Koehler, Kirsten; Harvey, Steven A.; Checkley, William; ,
Highlights: Exclusive use of liquefied petroleum gas saved participants 5.1 h per week. Participants with LPG cooked more hot meals per day, improving quality of life. Highly valued time savings were used for chores, leisure, and agricultural work. This study provides quantitative evidence that cooking with LPG saves time. Abstract: Background: Efforts to promote clean cooking through adoption of clean-burning fuels such as liquefied petroleum gas (LPG) are often based on the idea that near-exclusive use of LPG could lead to health improvements. However, benefits beyond health, such as time savings, could be more tangible and meaningful to LPG users. Objectives: This study investigated the effect of an LPG intervention on time spent cooking and collecting fuel, using objective measures of stove temperatures combined with self-reports under conditions of near-exclusive LPG use. We also investigated the perceived value of any time savings and potential economic and quality of life implications. Methods: We analyzed data from the Cardiopulmonary outcomes and Household Air Pollution trial in Puno, Peru, a randomized controlled trial with 180 participants assessing exposure and health impacts of an LPG stove, fuel, and behavioral intervention. Surveys conducted with 90 intervention women receiving free LPG and 90 control women cooking primarily with biomass assessed time spent cooking and collecting biomass fuel and use of time savings. Cooking time was objectively measured with temperature sensors on all stoves. Qualitative interviews explored perceptions and use of time savings in more depth. Results: Intervention women spent 3.2 fewer hours cooking and 1.9 fewer hours collecting fuel per week compared to control women, but cooked on average 1.0 more meals per day. Participants perceived time saved from LPG positively, reporting more time for household chores, leisure activities, and activities with income-generating potential such as caring for animals and working in fields. Discussion: This paper suggests that the benefits of LPG extend beyond health and the environment. LPG use could also lead to economic and quality of life gains, through increased time for work, rest, and consumption of hot meals, and reduced arduous biomass fuel collection.